LOYALITAS WISATAWAN TERHADAP KOTA BATAM SEBAGAI DESTINASI WISATA - Riki Andiko; Renza Fahlevi; Fitriana Aidnila Sinambela (POLITEKNIK LP3I JAKARTA, 2025)
Batam City is one of the areas that is a favorite tourist destination for domestic and foreign tourists. However, Batam City is considered better known as a transit city before tourists visit Singapore and Malaysia. This study aims to analyze the effect of destination performance and destination image on tourist satisfaction and loyalty to Batam City as a destination. This type of research is quantitative. The respondents of the study were tourists who had visited Batam City more than twice. The collection of research data using questionnaires and the collected data was analyzed using the SEM-PLS approach and assisted by SMARTPLS statistical software. The results of the study indicate that destination performance has an influence on destination image. Destination performance has a significant influence on tourist satisfaction with Batam City, while destination image has no influence on tourist satisfaction with Batam City. The results of this study also prove that satisfaction has a significant influence on tourist loyalty to Batam City as a tourist destination. The results of this study are expected to contribute to stakeholders to make strategic policies in increasing tourist loyalty to Batam City as a tourist destination.